2014
DOI: 10.1002/phy2.201
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride-sensitive fluid resorption in NCI-H441 lung epithelia depends on an apical Cl conductance

Abstract: Proper apical airway surface hydration is essential to maintain lung function. This hydration depends on well‐balanced water resorption and secretion. The mechanisms involved in resorption are still a matter of debate, especially as the measurement of transepithelial water transport remains challenging. In this study, we combined classical short circuit current (ISC) measurements with a novel D2O dilution method to correlate ion and water transport in order to reveal basic transport mechanisms in lung epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Our measurements cannot distinguish between these possibilities. These findings are broadly consistent with published results: in two studies CFTR inhibition caused a small decrease (NCI-H441 cells [39]) or no change (primary human type II cells [59]) in fluid absorption implying that CFTR-mediated Cl - absorption is not of primary importance while another study [11] found a small degree of CFTR-mediated Cl- secretion at baseline (~ 5% increase in TEPD following CFTR inhibition). In order to investigate the role of Cl - channels under stimulated conditions, NCI-H441 cells were treated with the cAMP agonist forskolin that can activate both ENaC and CFTR.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our measurements cannot distinguish between these possibilities. These findings are broadly consistent with published results: in two studies CFTR inhibition caused a small decrease (NCI-H441 cells [39]) or no change (primary human type II cells [59]) in fluid absorption implying that CFTR-mediated Cl - absorption is not of primary importance while another study [11] found a small degree of CFTR-mediated Cl- secretion at baseline (~ 5% increase in TEPD following CFTR inhibition). In order to investigate the role of Cl - channels under stimulated conditions, NCI-H441 cells were treated with the cAMP agonist forskolin that can activate both ENaC and CFTR.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies have used charcoal stripped serum instead of FBS which could offer better reproducibility [28, 39]. In our experiments there was little variation in the model characteristics with different batches of FBS.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The human lung adenocarcinoma cell line H441 is a well-established model for the investigation of pulmonary sodium transport processes (5,46,68,90). Cells were purchased from the American Type Culture Collection (distributed by LGC standards, Wesel, Germany) in the 65th passage and cultured exactly, as previously described (6).…”
Section: ϫ5mentioning
confidence: 99%